From Women’s Rights Lawyer in Pakistan to a Precarious Life in Australia: Learning From Lived Experience - Mrs Babar; Hartley, Lisa; Rachel, Burke; Rebecca, Field (Living Refugee Archive, University of East London, 2021)
Internationally the number of people displaced is at an historical high. The United Nations High Commissioner for Refugees (UNHCR) estimated that there were more than 79.5 million people displaced by conflict or persecution at the end of 2019 (UNHCR 2019). Australia is one of a relatively small number of countries that annually resettles refugees from overseas. In accordance with its international obligations under the UN Convention Relating to the Status of Refugees, Australia also provides protection to people who arrive in Australia seeking asylum. Historically, however, Australia’s policy response to people seeking asylum has been particularly punitive, including the re-introduction of temporary forms of protection for those found to be refugees.